2017
DOI: 10.5121/sipij.2017.8103
|View full text |Cite
|
Sign up to set email alerts
|

Robust Feature Extraction Using Autocorrelation Domain for Noisy Speech Recognition

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…ASR systems have principally focused on phoneme, word, hence sentence decoding and identification of speaker using various algorithms and techniques like LPC [8] [13] with Hidden Markov Model [14][16][18] [20] where they predict the output based on expectation maximization by reducing error. The ASR systems and speaker identification application includes auto correlation analysis and LPC analysis [8], [13], [12], it is revealed that features extracted using MFCC perform better compared to LPC [9] in speech recognition. With regard to acoustic feature extraction, researchers used Mel Frequency Cepstral Coefficients, since cepstral coefficients mimics human perception [2], [8], [4], [5], [10], [13].…”
Section: Objectivesmentioning
confidence: 99%
“…ASR systems have principally focused on phoneme, word, hence sentence decoding and identification of speaker using various algorithms and techniques like LPC [8] [13] with Hidden Markov Model [14][16][18] [20] where they predict the output based on expectation maximization by reducing error. The ASR systems and speaker identification application includes auto correlation analysis and LPC analysis [8], [13], [12], it is revealed that features extracted using MFCC perform better compared to LPC [9] in speech recognition. With regard to acoustic feature extraction, researchers used Mel Frequency Cepstral Coefficients, since cepstral coefficients mimics human perception [2], [8], [4], [5], [10], [13].…”
Section: Objectivesmentioning
confidence: 99%
“…However, the volume of the voice data files after the aggravation processing is often very large. Therefore, in order to reduce the burden of computer processing and improve the data processing capability, it is necessary to segment the speech signal [12]. Segmentation processing is a common method for computers to process general data, which is manifested in speech signals by dividing the signal into frames.…”
Section: Pre-emphasis and Framingmentioning
confidence: 99%
“…Disken et al [5] proposed an algorithm showed superior verification performance both with the conventional GMM-universal background model and universal background model (UBM) method, and the state of-the-art i-vector method. Farahani [6] discussed the robust features extractions using autocorrelation domain for noisy speech recognition. This paper depicted a straightforward and compelling strategy for diminishing the impact of clamor on the autocorrelation of the perfect flag.…”
Section: Literature Reviewmentioning
confidence: 99%